B Cell Responses in the Development of Mammalian Meat Allergy - Chandrasekhar, Jessica L.; Cox, Kelly M.; Erickson, Loren D. (Frontiers in Immunology, 2020)
Studies of meat allergic patients have shown that eating meat poses a serious acute health risk that can induce severe cutaneous, gastrointestinal, and respiratory reactions. Allergic reactions in affected individuals following meat consumption are mediated predominantly by IgE antibodies specific for galactose--1,3-galactose (-gal), a blood group antigen of non-primate mammals and therefore present in dietary meat. -gal is also found within certain tick species and tick bites are strongly linked to meat allergy. Thus, it is thought that exposure to tick bites promotes cutaneous sensitization to tick antigens such as -gal, leading to the development of IgE-mediated meat allergy. The underlying immune mechanisms by which skin exposure to ticks leads to the production of -gal-specific IgE are poorly understood and are key to identifying novel treatments for this disease. In this review, we summarize the evidence of cutaneous exposure to tick bites and the development of mammalian meat allergy. We then provide recent insights into the role of B cells in IgE production in human patients with mammalian meat allergy and in a novel mouse model of meat allergy. Finally, we discuss existing data more generally focused on tick-mediated immunomodulation, and highlight possible mechanisms for how cutaneous exposure to tick bites might affect B cell responses in the skin and gut that contribute to loss of oral tolerance.